(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Human capital has an impact on economic growth by several channels. This study presents a conceptual research model that we built starting from the economic increase models which explain the way in which the revenue per inhabitant was created taking into account mechanisms, channels and influence factors. I applied this model to the member states of the European Union and the results obtained confirmed the existence of some positive effects of human capital – expressed through education – on economic growth.